Sources of Economic Growth and Changes in Energy Consumption: Empirical Evidence for Taiwan (2004-2016) - Hong, Cheng-Yih; Yen, Yu-Shuang; Chien, Ping-Chieh (International Journal of Energy Economics and Policy, 2019)
Since the 1990s, Taiwan has promoted the upgrading of industrial structure, and the financial crisis has brought about major economic shocks. After Taiwan became a WTO member in 2002, the total trade volume increased significantly under the trade liberalization economic system. The trade sector has become the main source of Taiwan’s economic growth. As energy consumption expands with economic growth, the instability of international energy prices has become an important factor hindering Taiwan’s future economic development. Taiwan’s energy demand is over 99% dependent on imports, making Taiwan’s economic growth and energy consumption really closely related. This study has found that the source of growth has transformed from domestic final demand effect and exports effect to technical coefficients effect and self-sufficiency Coefficients effect. The financial crisis has increased the “self-sufficiency” coefficient effect and the technical coefficient effect, and all other industries except the “agricultural sector” have shown significant growth. On the other hand, the source of energy consumption has changed after the financial crisis. This also confirms that Taiwan’s economic growth is closely related to energy consumption, indicating that energy shortage has indeed had an important impact on Taiwan’s economic development. Keywords: source of economic growth, energy consumption, technical coefficient JEL Classifications: Q43, C6, E2, E210 DOI: https://doi.org/10.32479/ijeep.7453